Bird diversity of three islands in the Straits of Malacca - Ramli, Rosli; Azirun, Mohd Sofian; Hashim, Rosli (Malaysian Journal of Science, 2008)
Bird species diversity of three islands (pulau) in the Straits of Malacca was studied in 2004 and 2007. A total of 12 species of birds was recorded from Pulau Perak, 21 species from Pulau Jarak, and 9 species from Pulau Lalang. Avifauna of these islands not only show differences in species diversity but also in community structures. Among the islands, Pulau Jarak had the highest bird diversity while Pulau Perak had the lowest bird diversity. Although Pulau Perak had more birds, this was contributed by the two most abundant species, i.e. Brown Noddy (Anous stolidus) and Brown Booby (Sula leucogaster) which comprised 98.7% of the island’s bird population. On other islands, the most abundant species were White-bellied Sea Eagle, Haliaeetus leucogaster (31% in Pulau Jarak and 34.7% in Pulau Lalang) and Pied Imperial Pigeon, Ducula bicolor (17.5% in Pulau Jarak and 30.4% in Pulau Lalang). This study confirms several earlier records on distribution of certain unique and interesting components of the biodiversity of the islands. Kepelbagaian spesies burung di tiga pulau yang terletak di Selat Melaka telah dikaji pada tahun 2004 dan 2007. Sebanyak 12 spesies burung telah direkodkan di Pulau Perak, 21 spesies di Pulau Jarak, dan Sembilan spesies di Pulau Lalang. Avifauna di pulau-pulau ini bukan sahaja menunjukkan perbezaan dari segi kepelbagaian spesies malah juga dari segi struktur komuniti. Pulau Jarak mencatatkan kepelbagaian burung tertinggi manakala Pulau Perak mempunyai kepelbagaian burung terendah. Walaupun Pulau Perak mempunyai lebih banyak burung, tetapi ini hanya disumbang oleh dua spesies yang paling melimpah iaitu Burung Camar Angguk (Anous stolidus) dan Burung Dendang Laut (Sula leucogaster) yang membentuk 98.7% populasi burung di pulau tersebut. Di pulau-pulau lain, spesies paling melimpah adalah Lang Siput, Haliaeetus leucogaster (31% di Pulau Jarak dan 34.7% di Pulau Lalang) dan Pergam Rawa, Ducula bicolor (17.5% di Pulau Jarak dan 30.4% di Pulau Lalang). Kajian ini mengesahkan beberapa rekod awal mengenai keunikan taburan dan kepentingan komponen biodiversiti pulau.